2022
DOI: 10.1021/acssuschemeng.2c00920
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study of a Eutectic Solvent Reveals Hydrophobic Segregation and Lack of Hydrogen Bonding between the Components

Abstract: An in-depth study of the hydrophobic eutectic solvent formed by butylated hydroxytoluene (BHT) and L-menthol (MEN) in a 1:3 molar ratio has been carried out using an integrated approach that combines differential scanning calorimetry (DSC), attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy, small-and wide-angle X-ray scattering (SWAXS), and molecular dynamics (MD) simulations. The obtained data have been step-by-step compared to those collected on the eutectic formed by 3,5-di-tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 55 publications
2
19
1
Order By: Relevance
“…If the latter is confirmed, it indicates that BHT does engage in limited hydrogen bonding with MEN contrary to the reported findings. 6 Furthermore, at the studied composition of x BHT = 0.25 by the authors, a positive deviation to ideality is observed (assuming no cocrystal formation) that is consistent with the reported selfaggregation and poor intermixing of the components. By all accounts, the system of BHT + MEN cannot be classified as a deep eutectic solvent, and therefore, inferences derived from this system as to new mechanisms for DES formation must be nuanced.…”
supporting
confidence: 79%
See 4 more Smart Citations
“…If the latter is confirmed, it indicates that BHT does engage in limited hydrogen bonding with MEN contrary to the reported findings. 6 Furthermore, at the studied composition of x BHT = 0.25 by the authors, a positive deviation to ideality is observed (assuming no cocrystal formation) that is consistent with the reported selfaggregation and poor intermixing of the components. By all accounts, the system of BHT + MEN cannot be classified as a deep eutectic solvent, and therefore, inferences derived from this system as to new mechanisms for DES formation must be nuanced.…”
supporting
confidence: 79%
“…The obtained phase diagram shown in Figure (i) presents two eutectic points for x BHT ∼ 0.24 and 0.37 and (ii) suggests the formation of two cocrystals with approximate MEN:BHT stoichiometries of 2:1 and 1:1, although this requires further investigation. If the latter is confirmed, it indicates that BHT does engage in limited hydrogen bonding with MEN contrary to the reported findings . Furthermore, at the studied composition of x BHT = 0.25 by the authors, a positive deviation to ideality is observed (assuming no cocrystal formation) that is consistent with the reported self-aggregation and poor intermixing of the components.…”
contrasting
confidence: 50%
See 3 more Smart Citations